SOSIALISASI PROGRAM HIBAH CALON PERUSAHAAN BERBASIS TEKNOLOGI DI DESA POOWO KABUPATEN BONE BOLANGO - Titin Dunggio; Sindi Aulia A. Lamase; Hairul Bariyah (LPPM Universitas Bina Mandiri Gorontalo, 2022)
The technology-based prospective business grant program is one of the government's initiatives to support the development of technology-based businesses at the local level. This socialization was carried out in Poowo Village, Kabila District, Bone Bolango Regency, with the aim of increasing community understanding of funding opportunities, business capacity development, and the benefits of technology in increasing business competitiveness. This activity involved lecture methods, discussions, and technical training for village communities. The results of the activity showed high community enthusiasm to participate in this program, with an increase in their understanding of the importance of technological innovation in business development. This activity provides a strong foundation for the community to take advantage of grant opportunities and improve the local technology-based economy.